Análise e metodologia de projeto de conversores cc-cc isolados com comutação sob tensão nula: ponte-completa e duplo meia-ponte - Schmidt, Julio Maragano (2017)
This work presents a study of an isolated DC-DC converter with zero-voltage switching (ZVS) and phase-shifted (PS) applied to full-bridge (ZVS-PS-FB) and double half-bridge converters (ZVS-PS-DHB). The double half-bridge converter is introduced as an alternative to the fullbridge converter with the additional advantage of operating ZVS over full power range, as well as for full output voltage ranges (from zero to maximum voltage). One of the objectives of the design methodology is to find out the converter´s parameters operating at ZVS for the entire range of loads in the ZVS-PS-DHB and to obtain a wide range of ZVS operation for the ZVSPS- FB converter. Added to this, the project methodology seeks to reduce the total losses by converter´s stages by choosing the most appropriate components to meet the design objectives. It is proposed a methodology of optimization of the high frequency transformers design for each converter, whose procedure makes the choice of cores and their parameters, based on the modified area product method, which uses iterative processes in combination with rules of thumb. The methodology for designing the parameters of the output filter is described, as well as the considerations in choosing the switches of the inverters. As result, this work seeks to improve the efficiency of the studied converters and their performance in soft switching under zero voltage.